2017
DOI: 10.1080/14397595.2017.1404179
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of two novel capillaroscopy techniques in suspected scleroderma-spectrum disorders: A single-centre cross-sectional study

Abstract: New technologies, in this case utilising a smartphone camera, could help to improve accessibility to nailfold capillaroscopy, an important diagnostic tool and putative biomarker in scleroderma-spectrum disorders, whilst retaining accurate results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Dermoscopy (similarly to USB microscopy) is hand-held and therefore easily portable, but requires an attached camera for image capture and is more expensive (in the order of $1000–$2000) than a USB microcope. A recent study comparing nailfold capillary photographs taken with a ‘smartphone lens’ and with a ‘smartphone dermatoscope’ to widefield microscopy [ 20 ] highlighted the potential of low-cost, portable devices for use in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Dermoscopy (similarly to USB microscopy) is hand-held and therefore easily portable, but requires an attached camera for image capture and is more expensive (in the order of $1000–$2000) than a USB microcope. A recent study comparing nailfold capillary photographs taken with a ‘smartphone lens’ and with a ‘smartphone dermatoscope’ to widefield microscopy [ 20 ] highlighted the potential of low-cost, portable devices for use in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Fortuitously, there are a number of low cost and handheld devices such as dermatoscopes and ophthalmoscopes which achieve a good visualisation of the nailfolds at around 10-20-fold magnification (see Figure 2c). A number of studies directly comparing these techniques with WSM and NVC have found a reassuring concordance [10][11][12]. In particular, although the rate of "unclassifiable" images is higher, ample diagnostically relevant findings can be elicited, even if more subtle changes can be missed.…”
Section: Handheld Devices-ophthalmoscopes Dermatoscopes Usb Microscmentioning
confidence: 91%
“…Rapidly improving technology, particularly with the availability of USB microscopes or attachments for smartphones, can already achieve similar magnification to NVC and record images. This infers that these devices are going to become more commonplace [11]. An additional advantage with the handheld devices is that they can be easier to use in patients with finger deformities and in thumbs (or even toes) which are often not visualised in other techniques, although the additional information gleaned from these is not yet of clear clinical utility.…”
Section: Handheld Devices-ophthalmoscopes Dermatoscopes Usb Microscmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline NFC was available in 94 patients (total 687 images, median eight images per patient [interquartile range [7][8]; two patients excluded with insufficient image quality).…”
Section: Nailfold Capillaroscopy Characteristics At Baselinementioning
confidence: 99%